2015
DOI: 10.1016/j.jstrokecerebrovasdis.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 rs20417 Polymorphism Is Associated with Stroke and White Matter Disease

Abstract: Goals To investigate the effect of COX-2 polymorphism and its product, prostaglandin-E2 (PGE2), on stroke risk in an endemic area for Chagas disease. In a separate cohort, to investigate the effect of COX-2 polymorphisms on the total burden of cerebral white matter disease. Methods Cases were outpatients with ischemic stroke; controls were stroke-free subjects from two outpatient clinics (heart failure and caregivers of a movement disorders clinic). We extracted DNA from total blood to investigate the rs2041… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Prostaglandin-endoperoxide synthase (PTGS2), also known as COX-2, is a primary response gene that is associated with maintenance of homeostasis in normal tissues and regulation of inflammation (S. L. Ma et al, 2008). The association of COX-2 gene polymorphism with ischemic stroke was explained in a variety of research (Oliveira-Filho et al, 2015;Wu et al, 2016). It is common knowledge that NF-κB mediates genes encoding cytokine receptors and cytokines, as well as cell adhesion molecules which contribute to immunity and inflammation (St-Germain, Gagnon, Parent, & Asselin, 2004).…”
mentioning
confidence: 99%
“…Prostaglandin-endoperoxide synthase (PTGS2), also known as COX-2, is a primary response gene that is associated with maintenance of homeostasis in normal tissues and regulation of inflammation (S. L. Ma et al, 2008). The association of COX-2 gene polymorphism with ischemic stroke was explained in a variety of research (Oliveira-Filho et al, 2015;Wu et al, 2016). It is common knowledge that NF-κB mediates genes encoding cytokine receptors and cytokines, as well as cell adhesion molecules which contribute to immunity and inflammation (St-Germain, Gagnon, Parent, & Asselin, 2004).…”
mentioning
confidence: 99%
“…In the Atherosclerosis Risk in Communities (ARIC) study and one other study, the C allele of PTGS2 rs20417 was reported to be associated with higher risk of stroke in African Americans or Brazilian population [16,32]. In contrast, the C allele was associated with lower risks of myocardial infarction, ischemic stroke and carotid intima-media thickness in an Italian population [15,33].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the association of a functional polymorphism of PTGS2 rs20417 and TXA2R rs1131882 with the risk of cardiovascular disease or ischemic stroke [ 14 18 , 21 , 22 ]. In the Atherosclerosis Risk in Communities (ARIC) study and one other study, the C allele of PTGS2 rs20417 was reported to be associated with higher risk of stroke in African Americans or Brazilian population [ 16 , 32 ]. In contrast, the C allele was associated with lower risks of myocardial infarction, ischemic stroke and carotid intima-media thickness in an Italian population [ 15 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Multiple studies reported an association between PTGS2 genetic polymorphisms and IS risk. 18,19 Matrix metalloproteinases (MMPs), as a category of proteolytic zinc-dependent enzymes, play an important role in the degradation of the extracellular matrix and take part in the progression of atherosclerosis by triggering the migration and proliferation of smooth muscle cells and by causing destabilization of atherosclerotic plaques. 20 Previously, studies have reported that the MMPs protein levels elevate result in blood-brain barrier dysfunction and impact the extent of the infarct, [21][22][23] and the polymorphisms of MMPs have been evaluated in IS.…”
Section: Introductionmentioning
confidence: 99%